Hubungan Keterampilan Mencatat dengan Hasil Belajar Siswa - Lomanda, Wulandari Cristal; Sano, Afrizal; Yusri, Yusri (Universitas Negeri Padang, 2013)
Making note is important in the learning process. The existence of the note, will help the student to repeat the lesson. The research was descriptive correlational form was aimed at testing the relationship between skills notes and learning outcomes of students. The research sample was junior high school student 4 Padang Panjang totaling 83 students. Data collection tool was a questionnaire, data were analyzed by percentage and correlation techniques. The research findings indicate that there is a significant correlation (r 0.474) between skills notes and learning outcomes of students.Â Keyword: skills notes of students, learning outcomes.